2018
DOI: 10.1186/s12916-018-1028-4
|View full text |Cite
|
Sign up to set email alerts
|

Syrian refugees in Greece: experience with violence, mental health status, and access to information during the journey and while in Greece

Abstract: BackgroundSince 2015, Europe has been facing an unprecedented arrival of refugees and migrants: more than one million people entered via land and sea routes. During their travels, refugees and migrants often face harsh conditions, forced detention, and violence in transit countries. However, there is a lack of epidemiological quantitative evidence on their experiences and the mental health problems they face during their displacement. We aimed to document the types of violence experienced by migrants and refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 14 publications
1
119
2
4
Order By: Relevance
“…Clinically significant symptoms of anxiety and risk for PTSD were reported by 40% of the individuals with RP and by more than 60% of the asylum seekers. Similar differences due to residence status have been reported previously [19,20], and recent studies based on asylum seekers also show high prevalence [14,16,17]. High levels of anxiety are comprehensible considering the justified fear of repatriation, but PTSD can also be explained by this factor.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Clinically significant symptoms of anxiety and risk for PTSD were reported by 40% of the individuals with RP and by more than 60% of the asylum seekers. Similar differences due to residence status have been reported previously [19,20], and recent studies based on asylum seekers also show high prevalence [14,16,17]. High levels of anxiety are comprehensible considering the justified fear of repatriation, but PTSD can also be explained by this factor.…”
Section: Discussionsupporting
confidence: 80%
“…These groups are scarcely represented in the literature on refugee mental health, which predominantly includes individuals from Southeast Asia [2,3]. Since the outbreak of the war in Syria in 2011, some studies have provided insight in the mental health status of Syrian refugees [12][13][14][15][16][17] and a few recent studies, e.g., Nosè et al [18], have included refugees of various nationalities. However, the broader community of refugees arriving to Europe in 2015 and forward has not yet been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…To detect symptoms of anxiety, depression, and PTSD, the questionnaire was complemented by a pre-validated anxiety disorder screen (the Refugee Health Screener 15 or RHS-15) (Hollifield et al, 2013). The survey methodology and results for a subgroup of participants have been published in a companion article (Ben Farhat et al, 2018), which reports on violence and mental health of Syrian refugees in Greece. Results from the whole sample have been published in an internal report available online (Ben Farhat et al, 2017).…”
Section: Participants and Study Proceduresmentioning
confidence: 99%
“…Repression of physical integrity, involuntary separation from the original social context, relocation for unspecified periods of time, economic instability or isolation are all among factors that may lead to erosion of refugees' feeling of safety (Abdi 2005). Though numbers vary between contexts, the refugee-associated adversities result in a higher than in general population prevalence of post-traumatic stress disorder, anxiety and depression (Fazel et al 2005;Turrini et al 2017;Farhat et al 2018).…”
Section: Refugees and Safetymentioning
confidence: 99%
“…Refugee camps are generally understood in terms of the humanitarian aid they provide, but the stay in the camp can be an ambivalent experience (Feldman 2015;Turner 2015). The standards of accommodation, hygiene, sustenance, access to health care as well as levels of protection and security vary greatly between the camps in Greece (Blitz et al 2017) and some camps have been found to be particularly detrimental to refugees' mental health and wellbeing (Farhat et al 2018). Furthermore, restrictions concerning entry requirements to third countries (Janmyr 2016), concerns about the legitimacy of the refugees (Feldman 2015), and the feeling of uncertainty that comes from a long stay in refugee camps (Coterill et al 2016;Grotti et al 2018), may have a negative effect on the individual sense of security.…”
Section: Camps and Safetymentioning
confidence: 99%